Selection of CNC Tool Combinations Through The Approach of Genetic Algorithm Methods with The Criteria of Minimizing Machining Time and Considering The Minimum Machining Gap - Yulianto, Irwan; Martikasari, Arida Murti (Universitas Insan Cendekia Mandiri, 2024)
The demand for products that require high precision is increasing. Therefore the production process with CNC machines is highly crucial. In the milling machining process, the roughing process takes the most time. The suitable selection of tools combination for the machining area will reduce the machining time. Roughing process sometimes cannot process the machining area with the minimum gap size. The research is to develop tools combination selection algorithm with the criteria of reducing machining time by considering the minimum gap in the workpiece machining area. The first stage is the preprocessing stage, which aims to initiate the tool size that can be used in the workpiece machining process and tools size grouping for the smallest gap machining process. The second stage is genetic algorithm (GA) stage, which aims to find the best tools combination according to the objective function. The sequence in the GA stage is determining initial solution, parents selection, crossover, mutation, regeneration, and determining the best solution. The developed algorithm has been tested on four workpieces. Characteristics of the features were tested on two closed pocket workpieces with island, each open pocket with island, and close pocket without island. Development of tools combination selection algorithm can assist in determining the best tools size to minimize the machining time.